Corporate Social Responsibility: A Study of the Hospitality Industry in Goa - De Souza, Christina Ana Maria; Pai, Mahesh Surendra (Prabandhan: Indian Journal of Management, 2013)
Goa is a famous tourist destination, and the hospitality industry forms a large part of the tourism industry in Goa. In recent years, many hotels in Goa have been consciously adopting corporate social responsibility initiatives. The present study is an investigation into the corporate social responsibility practices adopted by the hospitality industry in Goa. Six five - star hotels in Goa, three each from North and South Goa constituted the sample of the study. A triple approach to corporate social responsibility - employees, community, and the environment - was examined in the study, including the benefits arising out of undertaking corporate social responsibility initiatives, obstacles in promoting CSR, and the incentives that encouraged the hospitality industry to undertake and implement CSR practices and policies. The findings of the study reveal that the six hotels were undertaking corporate social responsibility for employees in the form of training them, paying attention to their health, and employing differently abled persons. For the community, few hotels showed interest in providing infrastructure and activities to ensure the empowerment of women. While most of the hotels provided food to the needy, none of the hotels made any attempt to provide low-cost housing to the poor. Most of the environment awareness programmes were organized on the World Environment day. The hotels perceived certain benefits as a result of taking up CSR practices such as good reputation for the hotel, awards, increase in positive brand image, and customer loyalty.